Analisis Yuridis Perceraian Luar Pengadilan di Desa Nyormanis Kecamatan Blega Kabupaten Bangkalan Madura - Kurnia Dwi Putri; Adinda Dian Eka Saputri; Nurul Firdausi; Luthfia Chairun Nisa (State Islamic University (UIN) of Sunan Ampel, 2019)
Law in Indonesian has regulated the procedures for marriage, divorce, and reconciliation in Law No. 1 of 1974 concerning Marriage. And also stated in Law No. 22 of 1946 concerning the Recording of Divorce and Referrals. From the explanation contained in the positive law, it can be seen that the meaning of divorce is the breaking of the marriage ties of a married couple as a result of the failure to carry out the marriage due to several things such as death and court decisions. Divorce in law of Indonesian must be announced before the court. The pronouncement of divorce before the court is a mandate from article 115 of the Compilation of Islamic Law (KHI) which reads “Divorce can only be conducted in front of a Religious Court hearing after the Religious Court has tried and failed to reconcile the two parties.” But in fact, there are still many Indonesian people who do divorce not before the court. Divorce which is done outside the court is very negative, especially for the wife. Divorce is done only by word alone without going through a pledge in front of the court, then the state does not want to recognize the divorce, so that if the wife wants to remarry with another person, then it cannot be done because the wife does not have an official divorce certificate from the court.